Insect Detection in Rice Crop using Google Code Lab - et. al., K. Sumathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Herb plants are essential in the medical field today and can help humans. Phyllanthus Elegans Wall is used in this study to analyse and categorize whether it is a safe or unhealthy leaf. At the moment, most insect identification methods rely on physical classification, making it difficult to automatically, quickly, and reliably identify in stored grains. The concept of this research is to ascertain the quality of leaves by combining technology with pesticide classification in the agricultural sector. Picture collection, image processing, and classification are the first steps in enhancing leaf quality analysis. The segmentation using HSV to input RGB image for the colour alteration structure is the most significant image processing method for this section. The colour and shape of a leaf disease image are used to analyse it. Insect detection in complex backgrounds is more versatile with the score map that is decision alternate highly interconnected layer, and our detection speed has upgraded. Finally, the taxonomy approach employs an algorithm that feeds directly that employs formation backwards techniques. The result shows a Many-layer Preceptor and Nonlinear Activation Feature comparison, as well as a percentage of accuracy contrast between MLP and RBF. MLP and RBF are neural network algorithms. Clearly, the Neural Network classifier has a better presentation and precision.